Elucidating risk factors for oral leukoplakia affecting gingivae in Japanese subjects. (15th June 2016) - Nagao, Toru; Warnakulasuriya, Saman; Hasegawa, Shogo; Sakuma, Hidenori; Miyabe, Satoru; Komaki, Kanji; Ishii, Koh; Machida, Junichiro; Kimura, Masashi; Kuroyanagi, Norio; Saito, Terumi; Takeuchi, Go; et al.
Background: Clinicopathological studies have revealed some distinct anatomical variations in the clinical presentation of oral leukoplakia (OL). Screening studies have shown that gingival leukoplakia (GL) to be more common among the Japanese. Objective: A hospital-based case-control study was undertaken among patients diagnosed with OL to compare clinico-pathological data between GL and OL affecting other sites (n-GL). Methods: One hundred fifty-one subjects attending four city hospitals in Japan diagnosed with OL were recruited to this study. OL was diagnosed by World Health Organization criteria. They were interviewed for risk factors, clinical presentations were charted and investigated by patch testing for allergy to dental materials and by biopsy for dysplasia. Results: Eighty-eight with GL and 63 with n-GL were included in the study. GL lesions were predominantly white (93%) though n-GL leukoplakia had red (speckled) foci in 26%. Eighty percent of GL were seen in association with prosthesis or restorations. There were no significant differences by age or in tobacco and alcohol use in the two groups. Metal allergy test was positive in 58% of the GL but was not significantly higher compared to the n-GL (41%). Histopathological features showed that inflammatory cell infiltrate was predominant in n-GL group ( p = 0.021). Higher dysplasia grades were also found in n-GL ( p = 0.018). During follow-up, nine oral cancers (14%) were detected in n-GL group and among GL cases four developed oral carcinomas (5%) ( p = 0.043). Cox hazard regression analysis revealed that after adjusting for age and sex, GL group was found to have a lower malignant risk, with a hazard ratio of 0.89 (95% CI: 0.51–1.04) when compared to n-GL. Conclusions: GL was more benign compared to n-GL in Japanese subjects, though risk factors appear similar. Further study is warranted to ascertain whether trauma may play an important role for hyperkeratinization of gingival tissues and possible evolution of GL to proliferative verrucous leukoplakia in later years.